From Cart to Click: Understanding Consumer Attitude towards Technology Enabled Online Grocery Shopping - Aggarwal, Deepshikha; Sharma, Deepti; Saxena, Archana B (Science and Technology - Recent Updates and Future Prospects Vol. 6, 2024)
Online grocery shopping is trending worldwide as one of the most expedient e-commerce practices. Many people have started purchasing their groceries online and this has allowed the researchers to identify and analyse the factors that influence the consumers for making online purchases. We have observed that until around 5 years back, the daily grocery requirements of the Indian consumers were fulfilled by the local Kirana store and to some extent by the emerging hypermarkets/supermarkets. But, with the popularity of the internet and the penetration of smartphones into the daily lives of people, several online grocery stores have been able to penetrate the Indian markets. The busy lives of people especially the urban working population, make online grocery shopping a popular choice. With traditional households still being widely spread in Indian society, online companies need to have a resounding approach to influence the buying habits and shopping patterns of consumers. The aim of this study is to understand the attitude of Indian consumers toward online grocery shopping and determine the factors that influence the consumer decision making to shop for groceries online. In this paper, we have comprehensively explored different areas associated with online grocery shopping and this study can be advantageous for online grocery retailers to articulate effective policies to gain customer confidence toward online grocery shopping. First, in-depth interviews with 20 to 25 people were conducted to have an overall impression of the views of Indian consumers on shopping the groceries online. Then, a survey with a well-thought-out questionnaire was circulated to around 150 people. The total number of complete responses was collected from 125 people. The primary data was collected and analysed to determine the consumer attitude towards online grocery shopping. The findings of the study show that the consumers are influenced by various factors like time-saving and convenience provided by online grocery shopping platforms. The result indicated that 64% of the respondents shop for groceries online, yet a considerable population was still comfortable shopping through the traditional brick-and-mortar stores. They are also influenced by the quality of products and the return policy as well as the level of comfort while using the online shopping website/ app. We have also been able to understand the reasons that prevent people from online shopping. Some people find themselves lacking the technical skills to shop online, but most people who do not shop online like going to the market personally. In the case of online shopping, an area of concern for most shoppers is trusting online applications. People are concerned about the privacy of their personal information while shopping online and need the thoughtfulness of the retailers to encourage more consumers to opt for online shopping platforms.